2018
DOI: 10.1111/camh.12269
|View full text |Cite
|
Sign up to set email alerts
|

The direct and indirect effect of attachment insecurity and negative parental behavior on anxiety in clinically anxious children: it's down to dad

Abstract: Background Theoretically, insecure attachment and negative parental behaviors are risk factors for childhood anxiety. However, few empirical studies have examined their relative contribution including differences between mothers and fathers. To date, only one study has examined a mediational model including these factors, albeit in a nonclinical sample. Method This study ameliorates this limitation by investigating direct and indirect relations between maternal and paternal attachment and behaviors, and clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
(116 reference statements)
2
13
0
Order By: Relevance
“…The results are consistent with findings of past studies which found that children with secure attachment have lower levels of behavioral adjustment problems such as depressive, anxiety and aggressive (Demby et al, 2017;Katsurada et al, 2017;Ensink et al, 2019;Spruit et al, 2020). While children with insecure attachment may leads to more behavioral adjustment problems (Madigan et al, 2013;Breinholst et al, 2019;Khan et al, 2020) such as internalizing problems (Katsurada et al, 2017) and externalizing problems (Nunes et al, 2013). The present results supported by the attachment theory Attachment Theory (Ainsworth 1973;Bowlby, 1969), and ecology system theory (Bronfenbrenner, 1979) which concluded that the bonding and interaction between mother and child was large influence on children's psychological outcomes.…”
Section: Disucssionsupporting
confidence: 92%
“…The results are consistent with findings of past studies which found that children with secure attachment have lower levels of behavioral adjustment problems such as depressive, anxiety and aggressive (Demby et al, 2017;Katsurada et al, 2017;Ensink et al, 2019;Spruit et al, 2020). While children with insecure attachment may leads to more behavioral adjustment problems (Madigan et al, 2013;Breinholst et al, 2019;Khan et al, 2020) such as internalizing problems (Katsurada et al, 2017) and externalizing problems (Nunes et al, 2013). The present results supported by the attachment theory Attachment Theory (Ainsworth 1973;Bowlby, 1969), and ecology system theory (Bronfenbrenner, 1979) which concluded that the bonding and interaction between mother and child was large influence on children's psychological outcomes.…”
Section: Disucssionsupporting
confidence: 92%
“…Although the importance of both parents is evident, often research within the attachment literature focuses primarily on attachment with the mother and not the father (e.g., Emerson, Donenberg, & Wilson, ; Frigerio et al, ; Gandhi et al, ). However, the importance of including paternal attachment when examining various health outcomes has been discussed (Breinholst, Tolstrup, & Esbjørn, ). As such, if paternal attachment can have implications for health outcomes, it is important that future research ensure that father relationships are incorporated into attachment research so that we can better understand the effect of parental attachment for health.…”
Section: Discussionmentioning
confidence: 99%
“…Critically, our sample did not include fathers. This is an important omission as there is evidence to suggest that fathers' and mothers' behaviours may be differentially associated with child anxiety (Breinholst et al, 2019;van der Bruggen et al, 2008;Verhoeven et al, 2012). Our study was also restricted in the variability of life events experienced, as participating families were largely homogeneous in terms of ethnicity and socio-economic backgrounds.…”
Section: Maternal Behaviour Presentation Taskmentioning
confidence: 99%